Allergy and parasites: the measurement of total and specific IgE levels in urban and rural communities in Rhodesia - Merrett, T G; Merrett, J; Cookson, J B (Clinical allergy, 1976)
Eighty adult asthmatics living in an African city had a significantly higher serum IgE level (799 u/ml) than the control group (350 u/ml). A high proportion (78.7%) of the asthmatics had demonstrable circulating mite-specific IgE antibodies. The rural population of a filariasis endemic region was investigated and although no allergic subjects were identified, the group had a significantly higher IgE level (1613 u/ml) than the asthmatics and also showed a relatively high incidence of grass pollen-specific IgE antibodies (35%). The discrepancy between clinical history and laboratory results supports the mast cell saturation hypothesis and suggests: (a) an explanation for the susceptibility to allergy of African and Asian immigrants to Great Britain, and (b) a practical approach for preventing allergic reactions in vivo.